The Influence of Using Weblog Toward Students Ability in Writing Recount Text - Selviana Bhudu (Foremost Journal, 2021)
ABSTRACT The goal of this study is to determine whether there was an influence of weblog on students' writing ability in writing recount text at SMAN 10 Kota Tangerang in the tenth grade. There were 286 students in total. The writer used purposive sampling to select the sample of 34 students for this study. This study used a quasi-experiment research design by using pre-test and post-test with quantitative approach. Students’ test was used by the writer to collect the data. Based on hypotheses testing, it is known that sig (0,000) is smaller than 0.05. This shows that zero hypotheses (Ho) was rejected and the hypotheses alternative (Ha) was accepted. So, the writer concluded that there was a significant influence of weblog toward students’ writing ability in writing recount text at tenth grade students of SMAN 10 Kota Tangerang.